The Effect Of Promotion And Product Quality On Purchase Decisions - Putri Handayani; Muslih Muslih (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study is to analyze and find out the influence between Promotion and Product Quality on Purchasing Decisions at PT. Smartfren Telecom, Tbk, medan. While the sample used accidental sampling is a sampling method carried out using anyone who was met by chance as a sample, for this study was 100 people. The data collection technique uses primary data in the form of questionnaires and uses a likert scale in the selection of selection responses, while the data analysis technique uses multiple linear regression analysis, classical assumption tests, hypothesis tests and coefficients of determination. Data processing in this study used the SPSS (Statistical Package for the Social Sciens) software program version 22. The conclusion of the study that positive promotion variables have auh effect and are partially significant in purchasing decisions. Thenthe variable kuality has a positive and significant effect on purchasing decisions. Andsimultaneously it can also be concluded that the variables X1 (Promotion), X2 (Product Quality) together affect the variable Y (Decisionn Purchase).Based on the results of the data analysis, the advice given to the company is that the company is expected to provide a better alternative in terms of product promotion and quality so that consumers can choose the product